Introductory students’ attitudes and approaches to Physics problem solving: Major, achievement level and gender differences - Nuri Balta (Journal of Technology and Science Education, 2019)
Students’ attitudes and approaches to problem solving are claimed to be related to their ways they learn physics and to their success in solving physics problems. In this study, the Attitudes and Approaches to Problem Solving (AAPS) survey was used to reveal Turkish introductory university students’ attitudes and approaches to physics problem solving. The data were collected from 175 students, in the spring semester of 2015-2016 academic year, from an introductory physics course at a university in the Black See Region of Turkey. The analysis of the data was conducted by grouping the data by major, achievement level, and gender. They are no statistically significant differences between the averages of civil engineering and molecular biology majors or between male and female students. However, we obtained a small sample correlation of 0.22 between students’ attitudes and exam grades that suggests high achievers’ attitudes and approaches to physics problems are more expert-like than the attitudes and approaches of low achievers. Implications for problem solving strategies and directions for further research are discussed.